Seroprevalence and risk factor modeling of Marek’s disease virus in indigenous Tilili breed chickens of the Amhara Region, Ethiopia - Berrie, K.; Jemberu, Wudu T.; Shite, A.; Admassu, B.; Melaku, A.; Birhan, M.; Getenet, K.; Fenta, M.D.; Kinde, M.Z.; Bitew, A.B.; Mulaw, A.; Mekasha, Y.T. (Elsevier, 2025)
This study aims to assess the seroprevalence and potential risk factors associated with Marek’s disease occurrence in indigenous Tilili breed chickens and its crosses. A cross-sectional serological study and questionnaire survey were conducted in seven districts of the Amhara region, Ethiopia, from November 2023 to June 2024. Using multi-stage sampling, 17 Kebeles (peasant associations) were selected from the seven districts. A total of 768 chicken sera were sampled and tested for presence of Marek’s disease virus antibodies using an indirect enzyme-linked immunosorbant assay test. According to the study, the overall apparent seroprevalence of MDV was 74.6%, with Ankesha district having the lowest prevalence (57.5%) and Banja district having the highest (93.8%).The prevalence varied significantly across the studied districts, and there was a statistically significant variation in disease distribution among the peasant associations. Key risk factors associated with Marek’s disease virus seropositivity in Tilili breeds included contact with other birds in the vicinity, sex, age group, and sanitation of the housing. However, factors such as breed, rearing method, and farming type were not significantly associated with Marek’s disease sero-status. This high seroprevalence of the disease in this chicken ecotype indicates active circulation of the virus in the area, underscoring the need for stringent control measures. Further molecular studies and identification of MDV DNA in active outbreaks is critical to characterize the circulating virus and assess the economic impact of the disease on these valuable indigenous chickens of Ethiopia.